2022
DOI: 10.3390/ijms23137043
|View full text |Cite
|
Sign up to set email alerts
|

Role of GDF15/MAPK14 Axis in Chondrocyte Senescence as a Novel Senomorphic Agent in Osteoarthritis

Abstract: Osteoarthritis (OA) is most prevalent in older individuals and exerts a heavy social and economic burden. However, an effective and noninvasive approach to OA treatment is currently not available. Chondrocyte senescence has recently been proposed as a key pathogenic mechanism in the etiology of OA. Furthermore, senescent chondrocytes (SnCCs) can release various proinflammatory cytokines, proteolytic enzymes, and other substances known as the senescence-associated secretory phenotype (SASP), allowing them to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…MAPK14 has also been reported as a specific target of regorafenib 46 . In this context, inhibition of the GDF15/MAPK14 pathway with a neutralizing anti-GDF15 antibody resulted in a senomorphic effect in senescent chondrocytes 47 . In addition, GDF15 expression is elevated in many pathological conditions, including COPD and idiopathic pulmonary fibrosis 48 .…”
Section: Discussionmentioning
confidence: 99%
“…MAPK14 has also been reported as a specific target of regorafenib 46 . In this context, inhibition of the GDF15/MAPK14 pathway with a neutralizing anti-GDF15 antibody resulted in a senomorphic effect in senescent chondrocytes 47 . In addition, GDF15 expression is elevated in many pathological conditions, including COPD and idiopathic pulmonary fibrosis 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Wen et al. ( 32 ) studied the role of the GDF15 /MAPK14 axis in the aging of chondrocytes in OA and found that GDF15 is a driving factor for chondrocyte aging and apoptosis and could promote the progression of OA by inducing angiogenesis. TLR7 is involved in immune responses in many inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Senescence and the associated SASP can affect cells within the tumor microenvironment (TME). The SASP was shown to promote tumorigenesis [ 66 ], EMT [ 67 , 68 , 69 ], cancer stemness [ 70 , 71 ], anticancer drug resistance [ 72 , 73 , 74 ], angiogenesis [ 75 , 76 , 77 , 78 ], immune suppression to promote tumorigenesis [ 79 , 80 ], and tumor suppression by the immune clearance of senescent cells [ 81 ]. Figure 4 shows the roles of the SASP, including tumor suppression and tumor promotion.…”
Section: Roles Of Sasp In Cancer Cell Proliferation and Therapeutic R...mentioning
confidence: 99%
“…This suggests that senescence can also promote tumorigenesis. CM of IL-1β (a component of SASP)-treated chondrocytes enhanced migration and the tube-forming potential of human umbilical vein endothelial cells (HUVEC) in a growth differentiation factor 15 (GDF15)-dependent manner [ 78 ]. CDK4/6 inhibitors induced senescence and increased the production of pro-angiogenic SASP factors such as VEGF, basic FGF (bFGF), PDGF, as well as multiple MMPs, resulting in vascular remodeling in preclinical models of pancreatic ductal adenocarcinoma (PDAC) [ 82 ].…”
Section: Roles Of Sasp In Cancer Cell Proliferation and Therapeutic R...mentioning
confidence: 99%